N'Dama cattle production in relation to nutritional interventions in villages in The Gambia - Riley, J.A.; Agyemang, K.; Dwinger, R.H.; Jeannin, P.; Grieve, A.S.; Little, D.A. (1988)
The experiments took place in the villages of Pirang (low trypanosomiasis risk), Keneba and Nioro Jattaba (low-to-medium trypanosomiasis risk). In Nioro Jattaba, cows milked once a day while in the other two villages cows milked twice a day. In Pirang and Keneba, 45 calves taken from each village divided into 3 treatment groups of 15 animals each in order to study the effect of groundnut supplementation on the growth rate and survival of young suckling calves. Group 1 with 69 cows calved between August and December 1986 and Group 2 with 69 cows calved between September 1986 and February 1987 were used for groundnut supplementation trials in NioroJattaba. Cows of each group were divided into three treatment groups based on initial liveweight and calving date. Both in Keneba and Pirang trials, there was no significant (p>0.05) difference observed in the total weight gained between the three treatment groups. But the provision of groundnut meal to lactating cows during 5 months of the dry season had a highly significant effect on the amount of body weight loss in the NioroJattaba trial of Group1. In Group 2 both levels of supplementation with groundnut meal during the last 3 months of the dry season reduced weight loss by 10kg. As in Group 1, feeding the cows improved the growth performance of their calves in Group 2 trial. Supplementation of lactating females resulted in an increase in milk output both in Group 1 and 2 cows in the Nirorjattaba trial.